1987
DOI: 10.1177/019459988709600214
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy

Abstract: A case of melanotic neuroectodermal tumor of infancy has been presented, and the etiology, clinical presentation, and management of this rare tumor have been discussed. The tumor may not be familiar to most otolaryngologists and should be included in the differential diagnosis of pediatric head and neck neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Concerning the treatment of MNTIs, some authors have suggested that wide surgical margins may not be necessary because tumour islets may regress spontaneously after incomplete excision. Numerous clinicians have advocated allowing residual portions of the tumour to remain when radical excision would be mutilating [15][16][17][18] . Shafer and Frissell reported that at the time of the operation it was impossible to tell whether the tumour had been completely excised, and their case was followed up for 66 months with no recurrence 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the treatment of MNTIs, some authors have suggested that wide surgical margins may not be necessary because tumour islets may regress spontaneously after incomplete excision. Numerous clinicians have advocated allowing residual portions of the tumour to remain when radical excision would be mutilating [15][16][17][18] . Shafer and Frissell reported that at the time of the operation it was impossible to tell whether the tumour had been completely excised, and their case was followed up for 66 months with no recurrence 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates have previously been reported varying between 10-15% [3][4][5][6][7][8] . However, a recent French multi-centre review reported a recurrence rate of 27% 2 , which is more in keeping with our series where exactly that percentage of cases recurred.…”
Section: Discussionmentioning
confidence: 99%
“…There is a slight male preponderance with a 6:4 male:female ratio presenting at a median age of 4.5 months old 1 . Surgery is the first line of treatment but there is no clear consensus on intraoperative margins and a relatively high rate of recurrence estimated between 10-27% in spite of their predominantly benign nature [2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of choice consists of complete surgical excision with margins and curettage of the underlying bone via a gingivo-buccal sulcus incision or a lateral rhinotomy approach in the case of a large and locally invasive tumour mass (Crocket et al, 1987). An early diagnosis and treatment are important to avoid invasion of important surrounding structures as the optic nerve, and to minimize the extent of bone and soft tissue destruction.…”
Section: Discussionmentioning
confidence: 99%